Correlation between Childhood Food and Physical Activities on the Old Age Health in Sangli District - Koshti, V.V.; Ashokan, K.V. (International Journal of Applied Sciences and Biotechnology, 2014)
The food in childhood determines the health in old age. We analyzed the difference in the food habit and physical activities of urban and rural children and their effect in the development of old age diseases. The consumption of breakfast is more in urban area than rural children, similarly the consumption of meals is more in rural children comparing to urban one and the consumption of dinner is more in urban than rural one. The leafy vegetable and non-leafy vegetable consumption is more by rural children as compared to urban, but underground stem consumption is more by urban children than rural one. Fish and mutton consumption is also more in the case of urban children as compared to rural children. The consumption of chicken is less in urban children as compared to rural children. This difference in the underground stem and non-vegetable food consumption may be reason behind the excess weight gain and more old age diseases in the urban area. These facts must be cross checked with other factors for better interpretation. Our study indicates that urban children involved in physical activities less time comparing to rural one (51, 37 minutes) respectively for less than 30 minutes. But rural people involved in physical activities greater than 1 hour or two hour is more. This shows that rural children getting better physical work than the urban counterpart. This difference in physical activity will correlate the old age disease. Therefore to prevent various diseases in old age and provide better old age life a well planned awareness program must be initiated in all the preprimary and primary educational institutes without delay DOI: http://dx.doi.org/10.3126/ijasbt.v2i3.10961 Int J Appl Sci Biotechnol, Vol. 2(3): 238-242